2014
DOI: 10.1111/jvim.12303
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Survival of Dogs with Adrenal‐Dependent Hyperadrenocorticism: A Comparison between Mitotane and Twice Daily Trilostane Treatment

Abstract: BackgroundTreatment of adrenal‐dependent hyperadrenocorticism (ADH) involves either surgical resection of the adrenal tumor or medical therapy. For many years, mitotane has been considered the medical treatment of choice for dogs with ADH.ObjectivesThe aim of this study was to determine survival and prognostic factors for dogs with ADH treated with mitotane and trilostane.AnimalsTwenty‐six dogs with ADH were included in the study.MethodsFourteen dogs were treated with mitotane and 12 dogs were treated with tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
3
30
1
1
Order By: Relevance
“…In a recently published paper including 20 canine NSATs, the tumour size and amount of growth at follow‐up exams were identified as negative predictive factors (Arenas et al . ). In the same retrospective study, the authors stated that a tumour size of 20 mm is the optimal cut‐off point for adrenalectomy (Arenas et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a recently published paper including 20 canine NSATs, the tumour size and amount of growth at follow‐up exams were identified as negative predictive factors (Arenas et al . ). In the same retrospective study, the authors stated that a tumour size of 20 mm is the optimal cut‐off point for adrenalectomy (Arenas et al .…”
Section: Discussionmentioning
confidence: 97%
“…In the same retrospective study, the authors stated that a tumour size of 20 mm is the optimal cut‐off point for adrenalectomy (Arenas et al . ). Other dimensional criteria in veterinary medicine can be represented by the reported differences between carcinomas and adenomas (Capen ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Older age and heavier weight are negative prognostic factors reported in several studies; higher one hour post-ACTH serum cortisol, weakness at presentation, hyperphosphataemia and severity of clinical signs have also been reported as negative prognostic indicators (Kintzer and Peterson, 1991;Barker et al, 2005;Clemente et al, 2007;Arenas et al, 2014;Fracassi et al, 2014). There are a small number of studies reporting use of alternative drugs to manage HAC.…”
Section: Medical Managementmentioning
confidence: 99%
“…Twicedaily trilostane appeared to have a more favourable outcome for the treatment of PDH compared to a mitotane adrenolytic protocol, having median survival times of 900 days and 720 days, respectively (Clemente et al, 2007). Both trilostane and mitotane have been used to treat AT and no study to date has reported significantly different survival times for either drug (Helm et al, 2011;Arenas et al, 2014).…”
Section: Medical Managementmentioning
confidence: 99%